Production performance and immune responses of broilers given single step down diet with inclution of citric acid as acidifier - Jamilah .; Suthama N; Mahfudz LD (Indonesian Center for Animal Research and Development (ICARD), 2013)
A research was conducted to examine the effect of lime and citric acid as acidifier with single step down feeding systems on immune response and production performance of broilers. Treatments applied were P0 (normal diet), P1 (single step down diet), P2 (single step down diet + citric acid 0.8%), P3 (single step down diet + lime acid 0.4% (6.9 ml/100g feed)) P4, (single step down diet + lime acid 0.8% (13.8 ml/100g feed)) and P5 (single step down diet + lime acid 1.2% (20.7 ml/100g feed)). The parameters measured in this research were immune responses (percentage of bursa fabricius, spleen and heterophile lymphocyte ratio/H-L ratio) and production performances (muscle protein mass, feed intake and body weight). Research was assigned in a completely randomized design with 6 treatments and 4 replications (8 birds each). Treatment was given one week until 6 week. The data were subjected to analysis of variance and continued to Duncan test at the level of 5% probability. The results showed that percentage of bursa fabricius were significantly (P < 0.05) different. Treatment P2 (0.13) showed the highest value and significantly different to that of compared to the others P1 (0.08), but the other treatments were the same. Percentages of spleen from treatments P0 and P1 were statistically different as compared to the others. HL ratio was the same among treatments P0, P1 and P3, but it was significantly different from those of treatments P2, P4 and P5. Based on the results of the present study it was concluded that inclusion of citric acid both natural and synthetic forms can improve immune responses and increase muscle protein mass especially due to the inclusion of synthetic citric acid. Key Words: Broiler, Step Down Diet, Acidifier, Immune Response, Production Performance